(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
One of the most important conditions for the education to be targeted to the requirements of modern times, as well as to be suitable for social orders, is determining the effective training technologies. Many socio-cultural institutions, including the training models of the traditional-cultural institutions and the traditional models of knowledge transfer can be urgent and effective in determining the effective learning technologies. In this sense, folklore has a great potential of use in the application of modern educational technologies with its own functional capabilities that played an important role during many centuries in the interaction of some individuals with one another, in the socialization of people and in the self-formation of society. It is known that in the traditional-cultural environment there were institutional aspects and structures of knowledge transfer. Before the appearance of the written language in the oral communication level the information, i.e. the gained experience and knowledge were passed with the empiric models from generation to generation by old people, wise elders who were the institutional aspects of the traditional culture. The training technologies of the traditional culture have the following peculiarities: • Unlike the religious training technologies, it is not dogmatic, it has a democratic nature. • Taking into consideration the vital situations it has an operative adaptation character. • It has a character of getting and transferring the knowledge empirically. • It has the ability of taking into consideration the individual abilities and character in the process of incessant learning and teaching. The appearance of the Internet which is considered the “apogee” of communication has caused the formation of new transformations of traditional folk culture, virtual folklore samples as in all other spheres. Of course, in modern times at the stage when the digital resources are growing, the methods and means of getting, transferring and mastering knowledge, as a whole, the formation of education has completely changed. That is why, we consider that it is possible to use the opportunities of folklore the potential of virtual folklore and digital folklore resources, in the of lifelong education and innovative educational concepts, in getting and teaching of knowledge. Because the folklore resources have unique opportunities in formation of socio-psychological essence of personality. There is a great need for the individual to adopt the folklore of this group to freely enter and become a member of various social groups without experiencing psychological complex and tension in all spheres of society. In this sense, one of the goals of modern education is to aim the growing new generations to promote stereotypes that are in harmony with human values and to free them from non-humanist and local stereotypes.